SEAttle-based Research of Chinese Herbs for COVID-19 Study: A Whole Health Perspective on Chinese Herbal Medicine for Symptoms that may be Related to COVID-19. (10th January 2022) - Taylor-Swanson, Lisa; Altschuler, Daniel; Taromina, Katherine; Anderson, Belinda; Bensky, Daniel; Cohen, Misha; Huang, Helen; Ma, Shouchun; Majd, Iman; Mitchell, Craig; Schnyer, Rosa N; Conboy, Lisa
Introduction: East Asian Medicine (EAM) is a Whole System medicine that includes Chinese herbal medicine (CHM). Chinese herbal medicine has been utilized to reduce symptom burden in infectious disease, with notable theoretical reformulations during pandemics of the 3rd, 13th, and 17th centuries. Today, Licensed Acupuncturists trained in CHM have utilized it to treat symptoms and sequelae of COVID-19. However, little is known about its use or efficacy by the public and health practitioners. Understanding and evaluating whole medicine systems of healthcare is inherently complex; there is international consensus for a descriptive, pragmatic approach. We are conducting a feasibility pilot study using a prospective, pragmatic, observational design using Whole Health and Whole Person perspectives. The complexity of COVID-19 reflects the impact on multiple homeoregulatory systems and provides a unique opportunity to assess the impact of interventions such as EAM on whole health. Observation of these EAM encounters will provide valuable qualitative and quantitative data on the interface of an extant Whole System medicine with a novel complex illness as a precursor to a randomized clinical trial. Methods: This ongoing study observes a CHM clinic offering telehealth consultations to a diverse patient population since April, 2020. Patients who report symptoms potentially related to COVID-19 disease are consented for standardized collection and analysis of demographic and clinical data from each clinical encounter. Results: To date, 61 patients engaged in 195 consultations (mean 3.3) with 49 reporting symptom resolution sufficient to complete treatment, and 4 withdrawals. Just over half (62%) were female, with an average age of 45.7 years. A wide variety of CHM formulas and EAM dietary and lifestyle modifications were provided. Discussion: Adequate recruitment and retention suggest feasibility of the intervention and data collection. The rich dataset may facilitate the construction of Whole Health models of CHM's clinical impact, as well as integrative inquiry into CHM's effects on symptoms.